Cyclization of Activated Methylene Isocyanides with Methyl N(N),N′-Di(tri)substituted Carbamimidothioate: A Novel Entry for the Synthesis of N,1-Aryl-4-tosyl/ethoxycarbonyl-1H-imidazol-5-amines - Dukanya, Dukanya; Swaroop, Toreshettahally R.; Rangappa, Shobith; Rangappa, Kanchugarakoppal S.; Basappa, Basappa (SynOpen, 2019)
Base-induced cyclization of active methylene isocyanides with carbamimidothioates for the synthesis of N,1-aryl-4-tosyl/ethylcarboxy-1H-imidazol-5-amines is reported. The diversity of the reactions is exemplified by using various carbamimidothioates obtained from symmetrical N,N-disubstituted, unsymmetrical N,N,N-trisubstituted, and unsymmetrical N,N-disubstituted thioureas. This diversity is further enriched by different isocyanides. A mechanism for the formation of the title compounds is proposed.
Keywords: imidazoles; isocyanides; cyclization; carbamimidothioate; oxazole